Fiber-reinforced phosphate-based thermal barrier gradient composite and method of making
Patent Information
- Application Number
- CN202611023855.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-10
AI Technical Summary
[0005]本发明所要解决的技术问题是针对现有技术存在的不足,提供一种纤维增强磷酸盐基防隔热梯度复合材料及其制备方法,该复合材料同时满足了轻量化、耐热冲击、高效防隔热、可重复使用的综合需求,有效解决了现有同类复合材料难以兼顾多性能指标、在极端高温环境下易失效、使用寿命短等技术痛点
本发明利用基体与纤维结构的梯度结构设计,制备的复合材料整体密度为1.2~1.6g/cm3,室温(25℃)弯曲强度≥45MPa,室温(25℃)导热系数≤0.07 W/(m·K);在1000℃与室温之间循环10次后,试样长度变化率≤0.15%,厚度变化率≤2%,重量变化率≤0.7%;经1200℃热考核10次后室温(25℃)弯曲强度≥38MPa,室温(25℃)导热系数≤0.07W/(m·K);外表面经1200℃烧蚀,内表面温度能够维持在200℃以下,线烧蚀≤5×10-4mm/s;综上,本发明复合材料同时满足了轻量化、耐热冲击、高效隔热、可重复使用的综合需求,有效解决了现有同类复合材料难以兼顾多性能指标、在极端高温环境下易失效、使用寿命短等技术痛点,填补了高温隔热轻量化复合材料领域的技术空白,具有显著的技术创新价值、工程应用前景和经济效益,同时,也为后续同类高性能复合材料的研发提供了可行的技术参考和理论支撑,推动高温复合材料领域的技术进步与产业升级。
Smart Images

Figure CN122518803B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermal protection materials technology, specifically relating to a fiber-reinforced phosphate-based heat-resistant gradient composite material and its preparation method. Background Technology
[0002] With the development of aerospace vehicle technology, higher requirements have been placed on the comprehensive performance of thermal protection materials. This has prompted the development of thermal protection materials towards high temperature resistance, thermal insulation, reusability, load-bearing capacity, and strong thermal compatibility. Phosphate-based composite materials are widely used in the field of thermal protection due to their excellent heat resistance. However, existing technologies, through a single homogeneous fiber-reinforced structure, cannot simultaneously meet the comprehensive requirements of lightweight, thermal shock resistance, and efficient thermal insulation.
[0003] To address this issue, existing research has introduced gradient structures, using multilayer composites to achieve gradient changes in material properties. However, conventional gradient design approaches involve layer-by-layer casting and multiple curing of phosphates with different functional phases (such as chopped fibers), or segmented casting of a multi-segment phosphate matrix into a fiber needle-punched felt followed by single curing. With the former, during the layer-by-layer casting and curing process, the functional phases undergo uncontrolled random floating or sinking within each layer, resulting in a lack of gradual transition in concentration differences and making it difficult to form a stable, reproducible gradient structure. Furthermore, the step-by-step casting and curing process leads to distinct interfaces between the layers, resulting in poor interfacial bonding. With the latter, different types of phosphate solutions are segmented and cast into different areas of the fiber needle-punched felt. However, at the boundaries between different functional layers, the phosphate matrix permeates through the pores of the fiber preform, causing blending between different functional phases. This blurs the intended gradient interfaces, easily leading to the functional phases being distributed beyond the designed area, making it impossible to construct a precise gradient structure on the fiber needle-punched felt. Therefore, neither of the above two methods can achieve precise control over the structure of phosphate gradient composite materials, resulting in their thermal insulation performance failing to fully achieve the expected effect.
[0004] In summary, existing technologies are still insufficient to simultaneously meet the comprehensive requirements of lightweight, thermal shock resistance, and efficient heat insulation. Therefore, it is necessary to further develop reusable heat insulation composite materials that meet the above requirements. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a fiber-reinforced phosphate-based heat-insulating gradient composite material and its preparation method, which simultaneously meets the comprehensive requirements of lightweight, thermal shock resistance, high-efficiency heat insulation and reusability, and effectively solves the technical pain points of existing similar composite materials, such as difficulty in achieving multiple performance indicators, easy failure under extreme high temperature environment and short service life.
[0006] To solve the technical problem proposed in this invention, this invention provides a fiber-reinforced phosphate-based heat-resistant gradient composite material, which includes, from the outside to the inside, a heat-resistant layer, a transition layer and a heat-insulating layer. The heat-insulating layer is composed of a first alumina fiber cloth and a first phosphate matrix; the first phosphate matrix is composed of ceramic particles and a phosphate solution. The transition layer is composed of a second alumina fiber cloth and a second phosphate matrix; the second phosphate matrix is composed of sodium silicate and phosphate solution. The heat insulation layer is composed of a third alumina fiber cloth and a third phosphate matrix; the third phosphate matrix is composed of hollow microspheres and phosphate solution.
[0007] In the above scheme, the areal density of the first alumina fiber cloth is greater than that of the second alumina fiber cloth, which is greater than that of the third alumina fiber cloth.
[0008] Furthermore, the first alumina fiber cloth is a three-dimensional fabric, preferably a 2.5D fabric, with a single-layer thickness of 0.65~0.8mm and an areal density of 800~840g / m³. 2 .
[0009] Furthermore, the second alumina fiber cloth is a twill fabric with a single-layer thickness of 0.2~0.35mm and an areal density of 220~380g / m³. 2 .
[0010] Furthermore, the third alumina fiber cloth is a mesh fabric with a single-layer thickness of 0.2~0.3mm and an areal density of 100~200g / m³. 2 .
[0011] In the above scheme, the phosphate solution is an aluminum chromium phosphate solution, wherein the mass fraction of aluminum chromium phosphate is 50%~65% and the viscosity is 40~150 mPa·s.
[0012] In the above scheme, the ceramic particles are one or more of zirconium oxide, lanthanum oxide, and tantalum oxide, with a particle size of 1~20μm.
[0013] In the above scheme, the modulus of the sodium silicate is 2.4 to 3.2 and the solid content is 38 to 50%.
[0014] In the above scheme, the hollow microspheres are one or more of hollow ceramic microspheres and hollow glass microspheres, with a particle size of 50~150μm and a bulk density of 0.3~0.5g / cm³. 3 .
[0015] In the above scheme, the heat-insulating layer is made by coating a single layer of first alumina fiber cloth with a first phosphate matrix and then stacking 2 to 4 layers. During coating, the mass ratio of the first alumina fiber cloth to the first phosphate matrix is 1:(1.5 to 1.7).
[0016] In the above scheme, the content of ceramic particles in the heat-resistant layer decreases gradually from the outside to the inside along the thickness direction. This gradient is achieved by controlling the mass ratio of ceramic particles and aluminum chromium phosphate solution in the first phosphate matrix.
[0017] Furthermore, in the first composite phosphate matrix used along the thickness direction of the heat-resistant layer from the outside to the inside, the mass ratio of ceramic particles to aluminum chromium phosphate solution decreases in a gradient of 0.5:1 to 0.2:1.
[0018] In the above scheme, the transition layer is made by coating a single layer of second alumina fiber cloth with a second phosphate matrix and then stacking 15 to 20 layers. The mass ratio of the second alumina fiber cloth to the second phosphate matrix during coating is 1:(1 to 1.5).
[0019] In the above scheme, the content of sodium silicate in the transition layer decreases gradually from the outside to the inside along the thickness direction. This gradient is achieved by controlling the mass ratio of sodium silicate and aluminum chromium phosphate solution in the second phosphate matrix.
[0020] Furthermore, in the second composite phosphate matrix used in the transition layer from the outside to the inside along the thickness direction, the mass ratio of sodium silicate and aluminum chromium phosphate solution decreases in a gradient from 0.2:1 to 0.1:1.
[0021] In the above scheme, the heat insulation layer is made by coating a single layer of alumina fiber cloth with a third phosphate matrix and then stacking 40 to 50 layers. The mass ratio of the alumina fiber cloth to the third phosphate matrix during coating is 1:(1.7 to 2).
[0022] In the above scheme, the content of hollow microspheres in the heat insulation layer increases in a gradient from the outside to the inside along the thickness direction. This gradient is achieved by controlling the mass ratio of hollow microspheres and aluminum chromium phosphate solution in the third phosphate matrix.
[0023] Furthermore, in the third composite phosphate matrix used in the insulation layer from the outside to the inside along the thickness direction, the mass ratio of hollow microspheres to aluminum chromium phosphate solution increases in a gradient from 0.05:1 to 0.1:1.
[0024] This invention also provides a method for preparing a fiber-reinforced phosphate-based heat-insulating gradient composite material, comprising the following steps: 1) After coating the single-layer alumina fiber cloth with the corresponding phosphate matrix, let it stand for 3-5 hours, and then stack it to obtain the preform of the gradient composite material. 2) After the preform of the gradient composite material is placed in a vacuum bag and vacuumed, it is placed in a hot autoclave for hot pressing and curing. The cured preform is then heat-treated to obtain fiber-reinforced phosphate-based heat-insulating gradient composite material.
[0025] In the above scheme, the hot pressing curing includes three stages of heat preservation in sequence: the first stage heat preservation temperature is 110~120℃ and the heat preservation time is 1~2h; the second stage heat preservation temperature is 170~180℃ and the heat preservation time is 3~3.5h; the third stage heat preservation temperature is 200~220℃ and the heat preservation time is 2~3h.
[0026] In the above scheme, the heating rate of the hot-press curing process is controlled to be 1~5℃ / min.
[0027] In the above scheme, when the hot-press curing reaches the second stage heat preservation temperature, a pressure of 0.3~0.5MPa is applied and the pressure is maintained until the hot-press curing is completed.
[0028] In the above scheme, the vacuum degree is maintained at ≥90% throughout the hot pressing curing process.
[0029] In the above scheme, the heat treatment temperature is 1000~1200℃, and the holding time is 20~30min.
[0030] In the above scheme, the heating rate during the heat treatment process is controlled to be 5~10℃ / min. In the above scheme, the overall density of the heat-insulating gradient composite material is 1.2~1.6 g / cm³. 3 The bending strength at room temperature (25℃) is ≥45MPa, and the thermal conductivity at room temperature (25℃) is ≤0.07 W / (m·K); after 10 heat tests at 1200℃, the bending strength at room temperature (25℃) is ≥38MPa, and the thermal conductivity at room temperature (25℃) is ≤0.07W / (m·K); after the outer surface is ablated at 1200℃, the inner surface temperature is maintained below 200℃, and the linear ablation is ≤5×10 -4 mm / s.
[0031] The main technical concept of this invention is as follows: To address the problems associated with two gradient processes—layer-by-layer casting with multiple curing stages and segmented casting with single curing—this invention proposes a novel gradient method. Utilizing continuous alumina fiber cloths of varying areal densities, combined with phosphate matrices of different compositions, a composite molding process involving coating, lamination, curing, and heat treatment is employed. This achieves independent design for each functional layer, avoiding blending between different functional layers. By coating the phosphate matrix onto the continuous alumina fiber cloth, particle settling caused by the casting process is avoided, ensuring uniform component distribution within the fiber cloth layer. Furthermore, by controlling the gradient changes in the composition of the coated matrix, a smooth transition between composition and structure is achieved, ensuring precise construction of the material gradient.
[0032] The gradient design employs a three-layer structure to achieve synergistic functions: an outer heat-resistant layer, a middle transition layer, and an inner insulation layer. The heat-resistant layer directly receives the impact of heat flow. By adding ceramic particles, volatile phosphorus elements released after heat treatment are actively captured and chemically combined, transforming them into high-temperature resistant substances. This prevents phosphorus volatilization loss and porosity caused by gas generation, improving the material's resistance to thermal erosion. Furthermore, the content of ceramic particles decreases gradually from the outside to the inside along the thickness direction, providing a slow transition in performance and effectively reducing internal stress, thus preventing structural failure due to abrupt changes in physical properties.
[0033] The transition layer serves as an intermediate layer between the heat-insulating and heat-resistant layers. Sodium silicate is added to this layer; on the one hand, the long-chain SiO3 in the sodium silicate... 2- The structure has an adsorption effect on the phosphate matrix, enhancing the adhesion of the slurry. Simultaneously, the excellent flow properties of water glass fill pores, reducing interfacial defects. Furthermore, during heat treatment, molten water glass can fill pores formed in the phosphate matrix due to the volatilization of small-molecule gases, maintaining the material's density at high temperatures. In the final composite material, water glass, constrained by the rigid phosphate network, also plays a role in toughening and stress relief. However, higher water glass content leads to greater shrinkage, resulting in cumulative shrinkage stress and increasing the likelihood of interfacial delamination. Therefore, setting a water glass gradient decrease can create a smooth transition in composition and structure, while mitigating the abrupt changes in interfacial density and thermal conductivity caused by direct layer superposition, which can lead to delamination and cracking, and allowing for a better transition in the phosphate ceramic network.
[0034] The insulation layer enhances insulation efficiency and balances overall density. The addition of hollow microspheres leverages their low thermal conductivity and low density to impart excellent insulation performance and achieve lightweighting. However, if the hollow microspheres are distributed throughout the material, the hollow structure collapses and forms pores under high-temperature heat flow, actually reducing insulation efficiency. Therefore, a separate insulation layer is used. Furthermore, to avoid a significant difference in thermal conductivity at the interface between the high-content hollow microspheres and the transition layer, creating a steep temperature gradient that would hinder interfacial bonding, the content of hollow microspheres increases gradually from the outside to the inside along the thickness direction. This better disperses heat flow within the insulation layer, ultimately achieving effective insulation at the highest concentration. This three-layer design allows the material to achieve better integrated heat insulation and protection.
[0035] In the material preparation process, the curing process employs a vacuum-assisted autoclave molding process for integrated molding. A vacuum system continuously removes water molecule gaseous byproducts, preventing porosity caused by gas retention. Simultaneously, the external pressure provided by the autoclave compacts the interlayer interfaces while protecting the hollow microspheres from breakage. This process achieves simultaneous curing of multi-layer structures and eliminates interface problems caused by step-by-step casting, constructing a dense and well-bonded interlayer interface, ensuring a gradient transition between different functional layers. To achieve reusability of the material at high temperatures, the cured material undergoes further heat treatment. After high-temperature treatment, the phosphate matrix reacts within the functional layers or reacts with added functional additives to generate new substances, synergistically achieving ablation resistance, heat insulation, and reusability. Specifically, the ceramic particles added to the heat-insulating layer react with phosphate to generate a more erosion-resistant substance. In the transition layer, sodium silicate is composited with phosphate, forming a phosphate ceramic network within and between layers, exhibiting a high-temperature stable structure and connecting the heat-insulating and heat-resistant layers to form a transition. The hollow microspheres added to the insulation layer do not react with phosphates, but the phosphates themselves are transformed into high-temperature resistant substances. Furthermore, the addition of hollow ceramic microspheres improves the insulation performance of the material and reduces the thermal conductivity.
[0036] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention utilizes a gradient structure design between the matrix and fiber structures to prepare a composite material with an overall density of 1.2~1.6 g / cm³. 3 The sample exhibits the following properties: Flexural strength at room temperature (25℃) ≥ 45 MPa; thermal conductivity at room temperature (25℃) ≤ 0.07 W / (m·K); After 10 cycles between 1000℃ and room temperature, the sample length change rate ≤ 0.15%, thickness change rate ≤ 2%, and weight change rate ≤ 0.7%; After 10 cycles of heat testing at 1200℃, the flexural strength at room temperature (25℃) ≥ 38 MPa; thermal conductivity at room temperature (25℃) ≤ 0.07 W / (m·K); After ablation at 1200℃, the inner surface temperature can be maintained below 200℃, with linear ablation ≤ 5 × 10⁻⁵. -4mm / s; In summary, the composite material of this invention simultaneously meets the comprehensive requirements of lightweight, thermal shock resistance, high-efficiency thermal insulation, and reusability. It effectively solves the technical pain points of existing similar composite materials, such as difficulty in achieving multiple performance indicators, easy failure under extreme high temperature environments, and short service life. It fills the technical gap in the field of high-temperature thermal insulation lightweight composite materials, and has significant technical innovation value, engineering application prospects, and economic benefits. At the same time, it also provides feasible technical reference and theoretical support for the subsequent research and development of similar high-performance composite materials, and promotes technological progress and industrial upgrading in the field of high-temperature composite materials. Attached Figure Description
[0037] Figure 1 This is a physical image of the gradient composite material prepared in Example 1.
[0038] Figure 2 The image shows the overall microstructure of the gradient composite material prepared in Example 1.
[0039] Figure 3 The image shows the layered microstructure of the gradient composite material prepared in Example 1.
[0040] Figure 4 Comparison of gradient composite material prepared in Example 1 before (a) and after (b) micro-wind tunnel ablation.
[0041] Figure 5 Temperature history curve of the first ablation cycle for the gradient composite material prepared in Example 1.
[0042] Figure 6 The temperature history curve of the inner wall after 10 ablation cycles of the gradient composite material prepared in Example 1. Detailed Implementation
[0043] To better understand the present invention, the following embodiments further illustrate the content of the present invention, but the content of the present invention is not limited to the following embodiments.
[0044] Example 1 The preparation of the continuous fiber reinforced phosphate-based heat-insulating gradient composite material of the present invention is specifically as follows: 1) Preparation of preforms for gradient composite materials The density of the four layers is 840 g / m³. 2The 2.5D alumina fiber woven fabric, with a single layer thickness of 0.75 mm, was coated with a phosphate matrix. During coating, the mass ratio of the alumina fiber woven fabric to the phosphate matrix was 1:1.5. The phosphate matrix used here consisted of zirconium oxide and phosphate solution. The zirconium oxide had a particle size of 5 μm and a purity of ≥99%, while the aluminum chromium phosphate solution had a mass fraction of 60% and a viscosity of 120 mPa·s. The difference was that the mass ratio of zirconium oxide to aluminum chromium phosphate solution in the phosphate matrix was 0.5:1, 0.4:1, 0.3:1, and 0.2:1 for the four layers, respectively. Take 20 layers with a density of 360g / m³ 2 Alumina fiber twill fabric with a single layer thickness of 0.35 mm was coated with a phosphate matrix. During coating, the mass ratio of alumina fiber twill fabric to phosphate matrix was 1:1.4. The phosphate matrix used here was composed of sodium silicate and phosphate solution. The sodium silicate had a modulus of 2.4 and a solid content of 50%, while the aluminum chromium phosphate solution had a mass fraction of 60% and a viscosity of 120 mPa·s. The difference was that the mass ratio of sodium silicate to aluminum chromium phosphate solution in the phosphate matrix was 0.2:1 for 6 layers, 0.15:1 for 8 layers, and 0.1:1 for 6 layers. Take 50 layers with a density of 180 g / m³ 2 Alumina fiber mesh, with a single layer thickness of 0.2 mm, was coated with a phosphate matrix at a mass ratio of 1:2. The phosphate matrix used consisted of hollow glass microspheres and a phosphate solution, with the hollow glass microspheres having a particle size of 50 μm and a bulk density of 0.3 g / cm³. 3 The aluminum chromium phosphate solution has a mass fraction of 60% and a viscosity of 120 mPa·s. The difference is that the mass ratio of hollow glass microspheres to aluminum chromium phosphate solution in the phosphate matrix is 0.05:1 for 10 layers, 0.7:1 for 20 layers, and 0.1:1 for 20 layers. After coating, let it stand for 3-5 hours, cut the regular fiber cloth, and then stack it. The coated alumina fiber woven cloth is stacked to form a heat-insulating layer, the coated alumina fiber twill cloth is stacked to form a transition layer, and the coated alumina fiber mesh cloth is stacked to form a heat-insulating layer. The stacked structure is such that the heat-insulating layer, transition layer and heat-insulating layer are stacked from the outside to the inside along the thickness direction. In addition, the content of zirconium oxide in the heat-insulating layer decreases in a gradient from the outside to the inside along the thickness direction, the content of sodium silicate in the transition layer decreases in a gradient from the outside to the inside along the thickness direction, and the content of hollow glass microspheres in the heat-insulating layer increases in a gradient from the outside to the inside along the thickness direction, thus obtaining a preform of gradient composite material. 2) Preparation of fiber-reinforced phosphate-based heat-insulating gradient composite materials After the preform of the gradient composite material was placed in a vacuum bag and evacuated, it was placed in an autoclave for hot-press curing. The hot-press curing process included three stages of successively increasing temperature: the first stage was at 120℃ for 1 hour; the second stage was at 180℃ for 3.5 hours; and the third stage was at 220℃ for 2 hours. Throughout the hot-press curing process, the vacuum level was maintained at ≥90%, and the heating rate was controlled at 1℃ / min. When the temperature reached 180℃, a pressure of 0.3MPa was applied and maintained until the hot-press curing was completed. The cured preform was then transferred to a muffle furnace and heated to 1000℃ at a rate of 5℃ / min, and held for 30 minutes to obtain the continuous fiber-reinforced phosphate-based heat-insulating gradient composite material.
[0045] Figure 1 The image shows a physical picture of the gradient composite material prepared in Example 1. As can be seen from the picture, the sample surface is not curled, the surface is relatively flat, the thickness is uniform, and the integrity is good.
[0046] Figure 2 The image shows the overall microstructure of the gradient composite material prepared in Example 1. As can be seen from the image, the structure exhibits three distinct layers: a surface heat-resistant layer, a middle transition layer, and an innermost heat-insulating layer. The overall molding is good, with clear interfaces between layers, no obvious internal delamination, and a compact overall structure.
[0047] Figure 3 The diagram shows the layered microstructure of the gradient composite material prepared in Example 1, where (a) is the heat-insulating layer, (b) is the transition layer, and (c) is the heat-insulating layer. In the heat-insulating layer, the particles are tightly bonded to the phosphate matrix and fill around the fiber bundles, showing good bonding among the three. In the transition layer, the liquid sodium silicate and phosphate mix well, exhibiting good wettability to the fibers, and no exposed fibers were observed. In the heat-insulating layer, hollow microspheres are well dispersed in the slurry, and the alumina fibers are tightly wrapped by the phosphate matrix, with no obvious gaps at the fiber-matrix interface.
[0048] Example 2 The preparation of the continuous fiber reinforced phosphate-based heat-insulating gradient composite material of the present invention is specifically as follows: 1) Preparation of preforms for gradient composite materials Take 4 layers with a density of 800g / m³ 2The 2.5D alumina fiber woven fabric, with a single layer thickness of 0.73 mm, was coated with a phosphate matrix. During coating, the mass ratio of the alumina fiber woven fabric to the phosphate matrix was 1:1.7. The phosphate matrix used here consisted of lanthanum oxide and phosphate solution. The lanthanum oxide had a particle size of 10 μm and a purity of ≥99%, while the aluminum chromium phosphate solution had a mass fraction of 50% and a viscosity of 100 mPa·s. The difference was that the mass ratio of lanthanum oxide to aluminum chromium phosphate solution in the phosphate matrix was 0.3:1 for two layers and 0.2:1 for two layers. Take 20 layers with a density of 238 g / m³ 2 Alumina fiber twill fabric with a single layer thickness of 0.2 mm was coated with a phosphate matrix. During coating, the mass ratio of alumina fiber twill fabric to phosphate matrix was 1:1.4. The phosphate matrix used here was composed of sodium silicate and phosphate solution. The sodium silicate had a modulus of 3.2 and a solid content of 40%, while the aluminum chromium phosphate solution had a mass fraction of 50% and a viscosity of 100 mPa·s. The difference was that the mass ratio of sodium silicate to aluminum chromium phosphate solution in the phosphate matrix was 0.2:1 for 6 layers, 0.15:1 for 8 layers, and 0.1:1 for 6 layers. Take 50 layers with a density of 200g / m³ 2 Alumina fiber mesh, with a single layer thickness of 0.3 mm, was coated with a phosphate matrix. During coating, the mass ratio of alumina fiber mesh to phosphate matrix was 1:1.7. The phosphate matrix used consisted of hollow ceramic microspheres and a phosphate solution, with the hollow ceramic microspheres having a particle size of 100 μm and a bulk density of 0.5 g / cm³. 3 The aluminum chromium phosphate solution has a mass fraction of 50% and a viscosity of 100 mPa·s. The difference is that the mass ratio of hollow ceramic microspheres to aluminum chromium phosphate solution in the phosphate matrix is 0.05:1 for 20 layers and 0.1:1 for 30 layers. After coating, let it stand for 3-5 hours, cut the regular fiber cloth, and then stack it. The coated alumina fiber woven cloth is stacked to form a heat-insulating layer, the coated alumina fiber twill cloth is stacked to form a transition layer, and the coated alumina fiber mesh cloth is stacked to form a heat-insulating layer. The stacked structure is such that the heat-insulating layer, transition layer and heat-insulating layer are stacked from the outside to the inside along the thickness direction. In addition, the content of lanthanum oxide in the heat-insulating layer decreases in a gradient from the outside to the inside along the thickness direction, the content of sodium water glass in the transition layer decreases in a gradient from the outside to the inside along the thickness direction, and the content of hollow ceramic microspheres in the heat-insulating layer increases in a gradient from the outside to the inside along the thickness direction, thus obtaining a preform of gradient composite material. 2) Preparation of fiber-reinforced phosphate-based heat-insulating gradient composite materials After the gradient composite material preform was placed in a vacuum bag and evacuated, it was placed in an autoclave for hot-press curing. The hot-press curing process included three stages of successively increasing temperature: the first stage temperature was 110℃, and the holding time was 2 hours; the second stage temperature was 170℃, and the holding time was 3.5 hours; the third stage temperature was 200℃, and the holding time was 3 hours. The vacuum degree was maintained at ≥90% throughout the hot-press curing process, and the heating rate was controlled at 1℃ / min. When the temperature reached 170℃, a pressure of 0.5MPa was applied and maintained until the hot-press curing was completed. The cured preform was then transferred to a muffle furnace and heated to 1000℃ at a rate of 5℃ / min, and held for 30 minutes to obtain a continuous fiber-reinforced phosphate-based heat-insulating gradient composite material.
[0049] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that the heat-insulating layer does not have a gradient design, and the mass ratio of zirconium oxide to aluminum chromium phosphate solution in the phosphate matrix coated with the alumina fiber woven fabric of the heat-insulating layer is 0.5:1.
[0050] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the transition layer is not gradient-designed, and the mass ratio of sodium silicate to aluminum chromium phosphate solution in the phosphate matrix coated with alumina fiber twill cloth in the transition layer is 0.2:1.
[0051] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that the hollow glass microspheres are distributed throughout the entire layer, i.e., they are added in the heat-insulating layer, transition layer, and heat-shielding layer. In the heat-insulating layer, the mass ratio of hollow glass microspheres to aluminum chromium phosphate solution is 0.05:1, and the addition of zirconium oxide is the same as in Example 1; in the transition layer, the mass ratio of hollow glass microspheres to aluminum chromium phosphate solution is 0.07:1, and the addition of sodium silicate is the same as in Example 1; in the heat-shielding layer, the mass ratio of hollow glass microspheres to aluminum chromium phosphate solution is 0.1:1.
[0052] The thermally insulating gradient composite materials prepared in each embodiment and comparative example were cut into specimens with a length of 100 mm and a width of 20 mm. The thermal shock resistance of the prepared thermally insulating gradient composite materials was tested according to the experimental requirements of GB / T 30873. A muffle furnace was heated to 1000℃, and the specimens were placed in the furnace and held at that temperature for 20 min. After the heating was completed, the specimens were allowed to cool naturally to room temperature in air. This process was repeated 10 times, and the dimensional and weight changes of the specimens were measured.
[0053] The heat-resistant gradient composite materials prepared in each embodiment and comparative example were cut into samples with a length of 80 mm and a width of 15 mm. The bending strength and thermal conductivity were tested according to GB / T 1449-2005 and GB / T 10297-2015. The composite materials after repeated heat testing at 1200℃ 10 times were also tested for bending strength and thermal conductivity.
[0054] Table 1 Performance Test Results
[0055] As can be seen from the data in the table, the thermal insulation gradient composite material prepared in the example has a low overall density, good thermal shock resistance, a sample length change rate ≤0.15%, a thickness change rate ≤2%, and a weight change rate ≤0.7%. Furthermore, the sample still maintains structural integrity after 10 cycles between 1000℃ and room temperature. Its room temperature (25℃) flexural strength is ≥45MPa, and its room temperature (25℃) thermal conductivity is ≤0.07 W / (m·K). After 10 cycles of thermal testing at 1200℃, its room temperature (25℃) flexural strength is ≥38MPa, and its room temperature (25℃) thermal conductivity is ≤0.07W / (m·K), meeting the comprehensive requirements of lightweight, thermal shock resistance, high-efficiency thermal insulation, and reusability.
[0056] Comparative Example 1, with its heat-insulating layer containing a single proportion of oxide particles, showed an increase in overall material density and room-temperature thermal conductivity. This was because the single-proportion particle filling created a continuous thermally conductive network within the material, eliminating the heat flow bottleneck caused by the low-filling density in the original gradient structure. Furthermore, comparing the flexural strength after 10 heat tests, Comparative Example 1 exhibited a lower flexural strength retention rate than Example 1, indicating that gradient design can mitigate the degradation of flexural performance during heat testing. Comparative Example 2, with its transition layer containing a single proportion of sodium silicate, experienced delamination during repeated heat testing. This was due to excessive sodium silicate leading to significant overall shrinkage, exceeding the interlayer bonding strength during heat testing cycles and causing delamination. This demonstrates that gradient design can mitigate this by adjusting the sodium silicate content, achieving dimensional stability. Comparative Example 3, with hollow glass microspheres distributed throughout, experienced collapse at higher temperatures in the heat-insulating layer, resulting in increased thermal conductivity. Moreover, the pores left by the hollow microspheres caused increased thickness variation during repeated heat testing, leading to decreased dimensional stability.
[0057] The heat-resistant gradient composite material prepared in Example 1 was cut into specimens with a length of 100 mm and a width of 100 mm. These specimens were tested in an arc wind tunnel, with one side of the heat-resistant layer subjected to heat flow scouring. The test was performed 10 times according to the standard heat flow curve. The standard heat flow curve conditions were: heating surface temperature 1200℃ and heating time 1200 s. During the micro-wind tunnel test, the temperatures of the heated surface and the back side were recorded in real time, and the changes in the mass and dimensions of the specimen were measured and recorded before and after the test.
[0058] Tests showed that the thickness of the test piece before burning was 20.05 mm, and after burning it was 19.53 mm. The linear ablation was 0.52 mm, and the linear ablation rate was 4.33 × 10⁻⁶. 4 mm / s. Figure 4 The image shows a comparison of the thermal insulation gradient composite material before (a) and after (b) ablation in a micro-wind tunnel. The ablated sample showed no bending, breakage, or obvious warping, indicating that the thermal insulation structure can withstand cyclic ablation at 1200℃ and has good heat protection and erosion resistance. Figure 5 The temperature history curve of the first ablation cycle of the heat-insulating gradient composite material shows that the outer wall temperature remained at around 1200℃ during the 1200s ablation time, while the inner wall temperature slowly rose from 0 to 193℃. As a heat-insulating structure, it effectively protected the internal structure and demonstrated excellent heat insulation performance. Figure 6 The temperature history curve of the inner wall of the heat-insulating gradient composite material after 10 ablation cycles shows that the internal temperature of the structure does not change much with the increase of the number of cycles during the 10 thermal ablation cycles. In the 10 repeated experiments with available data, the heat insulation performance of the structure remains at an excellent level and has excellent reusability.
[0059] The above embodiments are merely examples for clear illustration and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations, and any obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A fiber-reinforced phosphate-based heat-insulating gradient composite material, characterized in that, Along the thickness direction from the outside to the inside, it includes a heat-resistant layer, a transition layer, and a heat-insulating layer; The heat-insulating layer is composed of a first alumina fiber cloth and a first phosphate matrix; the first phosphate matrix is composed of ceramic particles and phosphate solution; the content of ceramic particles in the heat-insulating layer decreases gradually from the outside to the inside along the thickness direction. The transition layer is composed of a second alumina fiber cloth and a second phosphate matrix; the second phosphate matrix is composed of sodium silicate and phosphate solution; the content of sodium silicate in the transition layer decreases gradually from the outside to the inside along the thickness direction. The heat insulation layer is composed of a third alumina fiber cloth and a third phosphate matrix; the third phosphate matrix is composed of hollow microspheres and phosphate solution; the content of hollow microspheres in the heat insulation layer increases gradually from the outside to the inside along the thickness direction. The areal density of the first alumina fiber cloth is greater than that of the second alumina fiber cloth, which is greater than that of the third alumina fiber cloth. The third alumina fiber cloth is a mesh fabric with an areal density of 100-200 g / m². 2 ; The preparation method of the fiber-reinforced phosphate-based heat-insulating gradient composite material includes the following steps: 1) After coating the single-layer alumina fiber cloth with the corresponding phosphate matrix, let it stand for 3-5 hours, and then stack it to obtain the preform of the gradient composite material. 2) After vacuuming the preform of the gradient composite material in a vacuum bag, it is placed in an autoclave for hot pressing and curing. The cured preform is then subjected to heat treatment at a heating rate of 5~10℃ / min, and the temperature is raised to 1000~1200℃ and held for 20~30min to obtain fiber-reinforced phosphate-based heat-insulating gradient composite material.
2. The fiber-reinforced phosphate-based heat-insulating gradient composite material according to claim 1, characterized in that, The heat-insulating layer is made by coating a single layer of alumina fiber cloth with a first phosphate matrix and then stacking 2 to 4 layers. During coating, the mass ratio of the first alumina fiber cloth to the first phosphate matrix is 1:(1.5 to 1.7). In the first composite phosphate matrix used in the heat-insulating layer from the outside to the inside along the thickness direction, the mass ratio of ceramic particles to aluminum chromium phosphate solution decreases in a gradient of 0.5:1 to 0.2:
1.
3. The fiber-reinforced phosphate-based heat-insulating gradient composite material according to claim 1, characterized in that, The transition layer is made by coating a single layer of second alumina fiber cloth with a second phosphate matrix and then stacking 15 to 20 layers. During coating, the mass ratio of the second alumina fiber cloth to the second phosphate matrix is 1:(1 to 1.5). In the second composite phosphate matrix used in the transition layer from the outside to the inside along the thickness direction, the mass ratio of sodium silicate and aluminum chromium phosphate solution decreases in a gradient of 0.2:1 to 0.1:
1.
4. The fiber-reinforced phosphate-based heat-insulating gradient composite material according to claim 1, characterized in that, The heat insulation layer is made by coating a single layer of alumina fiber cloth with a third phosphate matrix and then stacking 40 to 50 layers. During coating, the mass ratio of the alumina fiber cloth to the third phosphate matrix is 1:(1.7 to 2). In the third composite phosphate matrix used in the thickness direction of the heat insulation layer from the outside to the inside, the mass ratio of hollow microspheres to aluminum chromium phosphate solution increases in a gradient of 0.05:1 to 0.1:
1.
5. The fiber-reinforced phosphate-based heat-insulating gradient composite material according to claim 1, characterized in that, The thickness of a single layer of the first alumina fiber cloth is 0.65~0.8mm, the thickness of a single layer of the second alumina fiber cloth is 0.2~0.35mm, and the thickness of a single layer of the third alumina fiber cloth is 0.2~0.3mm.
6. The fiber-reinforced phosphate-based heat-insulating gradient composite material according to claim 1, characterized in that, The first alumina fiber cloth is a three-dimensional fabric with an areal density of 800~840 g / m³. 2 The second alumina fiber cloth is a twill fabric with an areal density of 220~380 g / m². 2 The phosphate solution is an aluminum chromium phosphate solution, wherein the mass fraction of aluminum chromium phosphate is 50%~65% and the viscosity is 40~150 mPa·s.
7. The fiber-reinforced phosphate-based heat-insulating gradient composite material according to claim 1, characterized in that, The ceramic particles are one or more of zirconium oxide, lanthanum oxide, and tantalum oxide, with a particle size of 1-20 μm; the sodium silicate has a modulus of 2.4-3.2 and a solid content of 38-50%; the hollow microspheres are one or more of hollow ceramic microspheres and hollow glass microspheres, with a particle size of 50-150 μm and a bulk density of 0.3-0.5 g / cm³. 3 .
8. A method for preparing a fiber-reinforced phosphate-based heat-insulating gradient composite material as described in any one of claims 1 to 7, characterized in that, Includes the following steps: 1) After coating the single-layer alumina fiber cloth with the corresponding phosphate matrix, let it stand for 3-5 hours, and then stack it to obtain the preform of the gradient composite material. 2) After vacuuming the preform of the gradient composite material in a vacuum bag, it is placed in an autoclave for hot pressing and curing. The cured preform is then subjected to heat treatment at a heating rate of 5~10℃ / min, and the temperature is raised to 1000~1200℃ and held for 20~30min to obtain fiber-reinforced phosphate-based heat-insulating gradient composite material.
9. The method for preparing the fiber-reinforced phosphate-based heat-insulating gradient composite material according to claim 8, characterized in that, The hot-press curing process includes three sequentially increasing heat preservation stages: the first stage heat preservation temperature is 110~120℃, and the heat preservation time is 1~2h; the second stage heat preservation temperature is 170~180℃, and the heat preservation time is 3~3.5h; the third stage heat preservation temperature is 200~220℃, and the heat preservation time is 2~3h.
10. The method for preparing the fiber-reinforced phosphate-based heat-insulating gradient composite material according to claim 8, characterized in that, The entire hot-press curing process maintains a vacuum degree of ≥90%, and the heating rate is controlled at 1~5℃ / min during the heating process. When the second stage heat preservation temperature is reached, a pressure of 0.3~0.5MPa is applied and maintained until the hot-press curing is completed.